The Needs of New Nursing Students to Become Professionals; Explaining the Experiences of Students and Graduates - Sara Heydari; Zahra Namjou; Mahnaz Antikchi; Mahdi Askari zaman; Fatemeh Bakhshi (Journal of Medical Education and Development)
Introduction: New nursing students have diverse educational needs that must be recognized and met to transition to professionalization. This study examined the experiences of graduates and fourth-year nursing students to identify these needs to help educational authorities facilitate students' path to professionalization. Method: This study was conducted in 2024 at the Shahid Sadoughi School of Nursing and Midwifery in Yazd using qualitative content analysis. Data were collected via purposive sampling through a focus group discussion session and 15 semi-structured interviews with 29 nursing students and graduates. Data analysis was performed based on the Granham and Landman method, and its validity was confirmed with the Guba and Lincoln criteria. Results: The data analysis resulted in 458 primary codes, 84 main codes, eight subthemes, and three themes. The main themes and subthemes of the qualitative analysis included learning roadmap (educational configuration, academic self-efficacy), professional competence (professional commitment and values, professional system, socialization process), and personal development (self-directed learning, interpersonal skills, preparation for future professional path). Conclusion: The results of this study emphasize the need for a comprehensive and integrated approach to nursing education. The findings indicate that to facilitate professionalization, in addition to academic skills, personal and professional development should also be considered. These results can help educational program designers understand students' needs and design programs that better prepare them for professional roles. The implementation of these programs may enhance the quality of nursing services and community health.